ПРИМЕНЕНИЕ ВАРИАТОРНОЙ (CVT) И АВТОМАТИЧЕСКОЙ КОРОБКИ ПЕРЕДАЧ В СОВРЕМЕННЫХ АВТОМОБИЛЯХ (Multidisciplinary Journal of Science and Technology, 2026)
This paper presents a comparative analysis of continuously variable transmission (CVT) and torque converter automatic transmission (AT) systems in terms of energy efficiency, dynamic performance, and operational characteristics. Based on theoretical modeling, analytical calculations, and conditional experimental data, acceleration, torque transmission, fuel consumption, and service life were evaluated. The results show that the CVT system is superior in urban driving conditions in terms of fuel efficiency and smooth operation, whereas the AT system is more effective under high torque and initial acceleration conditions.